PENGARUH BERBAGAI KOMBINASI CAMPURAN SERBUK KAYU GERGAJIAN TERHADAP PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Marno, Marno; Yusran, Yusran; Erniwati, Erniwati (Jurnal Warta Rimba, 2015)
The objectives of this study were to investigate the effects of some sawdust combinationsas growth medium on the growth and the yield of white oyster mushroom (Pleurotus ostreatus). The research was conducted at Boyaoge village, Palu, Central Sulawesi from February to April 2013. This study used experimental method by Completely Randomized Design (CRD) with sixsawdust combination treatments, i.e; sawdust of Palapi (Heritiera sp.) and Cempaka (Elmerrilia sp.) (M1), Palapi (Heritiera sp.) and Gmelina (Gmelina arborea) (M2), Palapi (Heritiera sp.) and Durian (Durio sp.) (M3), Cempaka (Elmerrilia sp.) and Durian (Durio sp.) (M4), Cempaka (Elmerrilia sp.) and Gmelina (Gmelina arborea) (M5) and Durian (Durio sp.) and Gmelina (Gmelina arborea) (M6).The results showed that all combinations of sawdust significantly affected all growth variables assessed. Combination of Cempaka and Gmelina sawdust (M5) gave the higher of the number of fruiting bodies (5,8) and cap length (5,376 cm). Combination of Cempaka and Palapi sawdust (M1) gave the higher of cap diameter (10,028 cm). Hence, combination of Palapi and Gmelina sawdust (M2) gave the higher of fresh weight of fruiting bodies (98,6 g), while combination of Durian and Gmelina sawdust (M6) gave the higher of dry weight of fruiting bodies (5,8 g). Keywords: Growth Medium, Combination, Sawdust, Oyster Mushroom (Pleurotus ostreatus).